Different Principles of ADP-Ribose-Mediated Activation and Opposite Roles of the NUDT9 Homology Domain in the TRPM2 Orthologs of Man and Sea Anemone - Kühn, Frank; Kühn, Cornelia; Lückhoff, Andreas (Frontiers in Physiology, 2017)
A decisive element in the human cation channel TRPM2 is a region in its cytosolic C-terminus named NUDT9H because of its homology to the NUDT9 enzyme, a pyrophosphatase degrading ADP-ribose (ADPR). In hTRPM2, however, the NUDT9H domain has lost its enzymatic activity but serves as a binding domain for ADPR. As consequence of binding, gating of the channel is initiated. Since ADPR is produced after oxidative DNA damage, hTRPM2 mediates Ca2+ influx in response to oxidative stress which may lead to cell death. In the genome of the sea anemone Nematostella vectensis (nv), a preferred model organism for the evolution of key bilaterian features, a TRPM2 orthologue has been identified that contains a NUDT9H domain as well. Heterologous expression of nvTRPM2 in HEK-293 cells reveals a cation channel with many close similarities to the human counterpart. Most notably, nvTRPM2 is activated by ADPR, and Ca2+ is a co-agonist. However, the intramolecular mechanisms of ADPR gating as well as the role of NUDT9H are strikingly different in the two species. Whereas already subtle changes of NUDT9H abolish ADPR gating in hTRPM2, the region can be completely removed from nvTRPM2 without loss of responses to ADPR. An alternative ADPR binding site seems to be present but has not yet been characterized. The ADP-ribose pyrophosphatase (ADPRase) function of nvNUDT9H has been preserved but can be abolished by numerous genetic manipulations. All these manipulations create channels that are sensitive to hydrogen peroxide which fails to induce channel activity in wild-type nvTRPM2. Therefore, the function of NUDT9H in nvTRPM2 is the degradation of ADPR, thereby reducing agonist concentration in the presence of oxidative stress. Thus, the two TRPM2 orthologues have evolved divergently but nevertheless gained analogous functional properties, i.e. gating by ADPR with Ca2+ as co-factor. Opposite roles are played by the respective NUDT9H domains, either binding of ADPR and mediating channel activity, or controlling the availability of ADPR at the binding site located in a different domain.